The Influence of Liquidity, Implementation of Good Corporate Governance and Sales Growth on Financial Distress (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2021-2023 Period) - Jasmina Syafei; Syahda Falihah; Herman Gani (MUI Kota Pekanbaru, 2026)
This research aims to determine the effect of liquidity, implementation of good corporate governance and sales growth on financial distress (empirical study on property and real estate companies listed on the Indonesian stock exchange for the 2021-2023 period). This research sample was obtained using a purposive sampling technique, resulting in 64 samples obtained for the 2021-2023 research period. The type of data uses secondary data, data analysis uses classical assumption tests and hypothesis testing uses panel data regression analysis (pooled data) using the SPSS 25 tool. The results of this study show that the partial hypothesis calculation of variables shows that liquidity, managerial ownership, Institutional ownership and sales growth have a partial effect on financial distress. From the results of this research, the Determination Coefficient (R2) with a value of 0.219 was also obtained, meaning that 21.90% of financial distress disclosures were explained by the variables liquidity, managerial ownership, institutional ownership and sales growth. Meanwhile, the remaining 78.10% is influenced by other variables outside the research model.